86.5k views
1 vote
Need this done in a square root method and show me all the steps.​

Need this done in a square root method and show me all the steps.​-example-1
User Ryderpro
by
6.4k points

1 Answer

4 votes

Answer:

d=i√7, -i√7

Explanation:

-2d^2 -4=10 add 4 to both sides

-2d^2 = 14 divide each term by -2

d^2= -7 take the square root of each side to get rid of the exponent

d= = √-7 ( put a slash(short line above that = sign ) in the second equal sign)

d = =i√7

User Wizztjh
by
5.7k points